Soil Stress-Strain Behavior: Measurement, Modeling and Analysis A Collection of Papers of the Geotechnical Symposium in Rome, March 16-17, 2006 - Ling, Hoe I.; Callisto, Luigi; Leshchinsky, Dov; Koseki, Junichi (Solid Mechanics and Its Applications,, 2007)
This Publication is an outgrowth of the Proceedings for the Geotechnical Symposium in Roma, also known as Tatsuoka Symposium, which was held on March 16 and 17, 2006 in th Rome, Italy. The Symposium was organized to celebrate the 60 birthday of Prof. Tatsuoka. The occasion also provided a chance to honor Prof. Tatsuoka for his research achievement. Prof. Tatsuoka collaborated with many international researchers, and thus the most beautiful and historical city of Rome naturally became an ideal location for his friends, colleagues and former students from different parts of the world to meet and celebrate this special occasion. The generosity of the University of Rome "La Sapienza" directed all roads to Rome by providing the venue for the Symposium. Prof. Tatsuoka retired from the University of Tokyo at the end of March 2004 following a 30-year distinguished career in teaching, research and professional service. During his tenure at the University of Tokyo, he published over 300 papers and graduated about 30 PhD and 25 MS students. Prof. Tatsuoka continues his research and teaching at the Tokyo University of Science. Thus, the Symposium also congratulated his new endeavor.